XANES and EXAFS of dilute solutions of transition metals at XFELs. (7th August 2019) - Chatterjee, Ruchira; Weninger, Clemens; Loukianov, Anton; Gul, Sheraz; Fuller, Franklin D.; Cheah, Mun Hon; Fransson, Thomas; Pham, Cindy C.; Nelson, Silke; Song, Sanghoon; Britz, Alexander; Messinger, Johannes; et al.
Abstract : It is demonstrated that X‐ray absorption spectroscopy, both XANES and EXAFS, of solutions with millimolar concentrations of metal is possible using the femtosecond X‐ray pulses from XFELs with two different sample delivery methods, a Rayleigh jet and a drop‐on‐demand setup. Abstract : This work has demonstrated that X‐ray absorption spectroscopy (XAS), both Mn XANES and EXAFS, of solutions with millimolar concentrations of metal is possible using the femtosecond X‐ray pulses from XFELs. Mn XAS data were collected using two different sample delivery methods, a Rayleigh jet and a drop‐on‐demand setup, with varying concentrations of Mn. Here, a new method for normalization of XAS spectra based on solvent scattering that is compatible with data collection from a highly variable pulsed source is described. The measured XANES and EXAFS spectra of such dilute solution samples are in good agreement with data collected at synchrotron sources using traditional scanning protocols. The procedures described here will enable XFEL‐based XAS on dilute biological samples, especially metalloproteins, with low sample consumption. Details of the experimental setup and data analysis methods used in this XANES and EXAFS study are presented. This method will also benefit XAS performed at high‐repetition‐rate XFELs such as the European XFEL, LCLS‐II and LCLS‐II‐HE.